Environmental considerations in statutory urban planning in Malaysia : implications in practice - 194160 Foziah Johar; International Congress on Restrospect and Prospect of Planning in Asia at the Turn of the Century (5th : 1999 : Seoul) (Skudai : Universiti Teknologi Malaysia, 1999)
01